Wonders of Oud reveals the uniqueness of agarwood - Shalfarina, Shahriman (2019)
The uniqueness of agarwood is well known in our society. Its uses in various fields such as perfumes, cosmetics, traditional medicine, beverages, and architecture reveal nature’s secret of our country.